AaMYB1 and its orthologue AtMYB61 affect terpene metabolism and trichome development in Artemisia annua and Arabidopsis thaliana. (27th March 2017) - Matías‐Hernández, Luis; Jiang, Weimin; Yang, Ke; Tang, Kexuan; Brodelius, Peter E.; Pelaz, Soraya
Summary: The effective anti‐malarial drug artemisinin (AN) isolated from Artemisia annua is relatively expensive due to the low AN content in the plant as AN is only synthesized within the glandular trichomes. Therefore, genetic engineering of A. annua is one of the most promising approaches for improving the yield of AN. In this work, the AaMYB1 transcription factor has been identified and characterized. When AaMYB1 is overexpressed in A. annua, either exclusively in trichomes or in the whole plant, essential AN biosynthetic genes are also overexpressed and consequently the amount of AN is significantly increased. Artemisia AaMYB1 constitutively overexpressing plants displayed a greater number of trichomes. In order to study the role of AaMYB1 on trichome development and other possibly connected biological processes, AaMYB1 was overexpressed in Arabidopsis thaliana . To support our findings in Arabidopsis thaliana, an AaMYB1 orthologue from this model plant, AtMYB61, was identified and atmyb61 mutants characterized. Both AaMYB1 and AtMYB61 affected trichome initiation, root development and stomatal aperture in A. thaliana . Molecular analyses indicated that two crucial trichome activator genes are misexpressed in atmyb61 mutant plants and in plants overexpressing AaMYB1 . Furthermore, AaMYB1 and AtMYB61 are also essential for gibberellin (GA) biosynthesis and degradation in both species by positively affecting the expression of the enzymes that convert GA9 into the bioactive GA4 as well as the enzymes involved in the degradation of GA4 . Overall, these results identify AaMYB1/AtMYB61 as a key component of the molecular network that connects important biosynthetic processes, and reveal its potential value for AN production through genetic engineering. Significance Statement: The biosynthetic pathway of artemisinin, an antimalarial and anticancer substance, only takes place in Artemisia annua glandular trichomes; however artemisinin content in this plant is too low to cover worldwide demand for the product. New research has identified AaMYB1 transcription factor that positively affects not only AN biosynthesis but also, as its orthologue AtMYB61, affect gibberellin biosynthesis and trichome proliferation; two diverse but connected processes necessary for improving AN yield in planta .